2021
DOI: 10.1038/s41598-021-90189-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Impact of daily high dose oral vitamin D therapy on the inflammatory markers in patients with COVID 19 disease

Abstract: COVID 19 is known to cause immune dysregulation and vitamin D is a known immunomodulator. This study aims to objectively investigate the impact of Pulse D therapy in reducing the inflammatory markers of COVID-19. Consented COVID-19 patients with hypovitaminosis D were evaluated for inflammatory markers (N/L ratio, CRP, LDH, IL6, Ferritin) along with vitamin D on 0th day and 9th/11th day as per their respective BMI category. Subjects were randomised into VD and NVD groups. VD group received Pulse D therapy (tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 40 publications
0
77
0
6
Order By: Relevance
“…After a scrupulous literature search and a meticulous study selection process, we included 13 studies in the present meta-analysis [7][8][9][10][11][12][13][14][15][22][23][24][25], pooling data retrieved from 2933 patients with COVID-19 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a scrupulous literature search and a meticulous study selection process, we included 13 studies in the present meta-analysis [7][8][9][10][11][12][13][14][15][22][23][24][25], pooling data retrieved from 2933 patients with COVID-19 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…1). Of the 13 studies, 10 were observational studies [7-10, 12-14, 22-24], while 3 were RCTs [11,15,25]. Relevant studies where clinical outcomes were not reported in terms of ICU admission or mortality were excluded [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of COVID-19, vitamin D can be considered as a protective factor due to its role in regulating the production of pro-inflammatory cytokines from pulmonary epithelial cells and macrophages, as well as in suppressing the cytokine storm, which is associated with immunopathogenesis of SARS-Cov-2 infection [31] . These beneficial effects in improving COVID-19 outcomes have been experimentally demonstrated, and patients who received adjunctive Pulse D therapy (vitamin D) showed a significant reduction in inflammatory markers associated with the clinical course of disease [32] .…”
Section: Discussionmentioning
confidence: 96%
“…Although a multidrug regimen with prolonged duration is recommended for the treatment of NTM-PD, the treatment outcomes are still suboptimal [4]. Moreover, malnutrition, which is frequently seen in patients with NTM-PD [5][6][7][8], has been shown to be a poor prognostic factor by previous studies [9,10].…”
Section: Introductionmentioning
confidence: 99%